The Role of Islamic Counseling Guidance for Perpetrators of Domestic Violence - Nurahmah Wati; Nor Fatmah (AHKAM, 2026)
Domestic violence remains a persistent problem in Indonesia, producing long-term physical, psychological, social, and spiritual harm for victims, families, and communities. Although Islamic counseling has been proposed as a rehabilitative and preventive approach, field-based evidence on its application to domestic violence perpetrators remains limited. This study aims to explore how Islamic counseling rehabilitates domestic violence perpetrators and strengthens family resilience. Using a qualitative case study design, the research examined two perpetrator cases through in-depth interviews with counselors and mentors, direct observation of counseling sessions and community activities, and analysis of program documentation. The data were analyzed descriptively through data reduction, narrative presentation, and thematic synthesis. The findings indicate that perpetrators’ violent behavior was associated with poor emotion regulation, maladaptive learned responses, early or forced marital transitions, patriarchal norms, and limited communication skills. The counseling process integrated behavioral methods, including modeling, reinforcement, emotion-regulation training, social-skills training, and cognitive behavioral therapy techniques, with Islamic spiritual practices such as muhasabah, istighfar, and dhikr to foster self-awareness, cognitive restructuring, repentance, and intrinsic motivation for behavioral change. The intervention also involved family mentoring, community support groups, and religious leaders, enabling perpetrators to practice new relational skills while supporting normative shifts against violence. Critical program components included a modular medium- to long-term design, measurable targets, follow-up monitoring, counselor competence in clinical–religious integration, and victim-safety safeguards. Participants, including child witnesses, reported improved emotional stability, renewed religious engagement, and observable reductions in aggressive behavior; however, the findings are limited by the small sample size and local context. The study concludes that the systematic integration of behavioral and cognitive behavioral techniques with Islamic spiritual frameworks offers a promising approach for rehabilitating domestic violence perpetrators and rebuilding family resilience in Indonesian settings. This study contributes to Islamic counseling, family resilience, and domestic violence intervention literature by providing field-based insights into a culturally and religiously grounded perpetrator rehabilitation model, while larger-scale controlled studies are needed to test generalizability and refine intervention modules.